Establishment of micropropagation in dwarf napiergrass (Pennisetum purpureum Schumach) and estimation of somaclonal variation using flowcytometry analysis - Nafiatul Umami, N. Umami (2012)
We have established in vitro propagation system of dwarf napiergrass (Pennisetum puryureum Schum) via multiple-shoot clumps formation. Shoot apices as initial explants were isolated aseptically from shoot-tillers and cultured in yitro on solid Murashige Skoog (MS) medium. The most effective phytohormone treatment for multiple- shoot clumps induction was 0.1 mg/L 2,4-dichlorophenoxyacetic acid(2,4-D) plus 2.0 mg/L 6-benzylaminopuriue (BAP). The addition of 50 pM cupric sulfate (CuSO4) could increase the percentage of clump proliferation. Plant regeneration frequency was achieved 84% by culturing the clumps on solid MS medium containing 0.1 mg/L a-naphthalene acetic acid (NAA) and 2.0 mg/L BAP. All regenerants were succesfully grown up in soil. Comparison of result from morphological characteristics evaluation and DNA content using flow cytometry (FCM) analysis showed that in vitro regenerants did not reveal any significant difference compare with control plants.